Cost-effectiveness of antenatal corticosteroids and tocolytic agents in the management of preterm birth: A systematic review. (July 2022) - Sebastian, Elizabeth; Bykersma, Chloe; Eggleston, Alexander; Eddy, Katherine E.; Chim, Sher Ting; Zahroh, Rana Islamiah; Scott, Nick; Chou, Doris; Oladapo, Olufemi T.; Vogel, Joshua P.
Summary: Background: Preterm birth is a leading cause of neonatal mortality and morbidity, and imposes high health and societal costs. Antenatal corticosteroids (ACS) to accelerate fetal lung maturation are commonly used in conjunction with tocolytics for arresting preterm labour in women at risk of imminent preterm birth. Methods: We conducted a systematic review on the cost-effectiveness of ACS and/or tocolytics as part of preterm birth management. We systematically searched MEDLINE and Embase (December 2021), as well as a maternal health economic evidence repository collated from NHS Economic Evaluation Database, EconLit, PubMed, Embase, CINAHL and PsycInfo, with no date cutoff. Eligible studies were economic evaluations of ACS and/or tocolytics for preterm birth. Two reviewers independently screened citations, extracted data on cost-effectiveness and assessed study quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement. Findings: 35 studies were included: 11 studies on ACS, eight on tocolytics to facilitate ACS administration, 12 on acute and maintenance tocolysis, and four studies on a combination of ACS and tocolytics. ACS was cost-effective prior to 34 weeks' gestation, but economic evidence on ACS use at 34-<37 weeks was conflicting. No single tocolytic was identified as the most cost-effective. Studies disagreed on whether ACS and tocolytic in combination were cost-saving when compared to no intervention. Interpretation: ACS use prior to 34 weeks' gestation appears cost-effective. Further studies are required to identify what (if any) tocolytic option is most cost-effective for facilitating ACS administration, and the economic consequences of ACS use in the late preterm period. Funding: UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP), a cosponsored programme executed by WHO.